Peace operations seen from below : UN missions and local people - 9 (Bloomfield, CT : Kumarian Press, 2006)
"Cambodia, Somalia, Mozambique, Bosnia, Haiti, Sierra Leone - all have been the subject of interventions by armed UN units sent to stabilize societies riven by political and ethnic antagonism." "Apart from anecdotal reportage, little is known or has been investigated about how local inhabitants in these and other cities interact with and respond to peacekeepers in their midst. Most studies of post-conflict situations focus on political elites, the demobilization of armed groups and the question of whether externally determined criteria for state reconstruction have been met."
"In Peace Operations Seen from Below Beatrice Pouligny argues that much of what is being rebuilt in societies emerging from war - or in some cases what is continuing to be destroyed - often lies in the 'ordinary' daily lives of both local populations and the staff of UN missions. These on-the-ground realities are often overlooked by outsiders, yet they may prove to be as important as political negotiations at the 'center', debates in the UN Security Council or hearings before an International Criminal Court." "Central to Pouligny's study is the key role played by local interlocutors. Her close analysis of several UN interventions, based on first hand observation of how local people intermingle with UN soldiery and civilians, sheds light on a neglected but crucial dimension of international peace enforcement."--BOOK JACKET.
The new forms of peace operations -- International visions of war and peace -- Local geography of UN peace operations -- The sphere of political, military, and economic entrepreneurs -- Indigenous 'civil societies' -- 'Local' employees of UN operations -- Different interpretations of a peace operation's mandate -- Missions' (in)capacity to carry out their mandates -- Peacekeepers lost in complex environments -- The history of relations with the outside world -- Figures of intervention -- Factors of mobilisation against the UN -- Ideas of 'legitimacy' and 'impartiality' redefined by local conditions -- What local actors expect from the UN -- Highly volatile balance of power -- Neither 'indifferent' nor 'apathetic' : why local communities protect themselves from the peacekeepers -- The limits of imposed 'procedural democracy' in post-war societies -- The political non-sense of most economic reconstruction programs -- Ambiguities of peacekeepers' role in maintaining 'law and order' -- The forgotten dimensions of 'justice' and 'reconciliation' programs.
Includes bibliographical references (p. 277-288) and index.
Keywords: United Nations -- Peacekeeping forces; Peacekeeping forces -- Moral and ethical aspects; Humanitarian assistance